The Effect of Investment Decisions, Funding Decisions, and Dividend Policies on Company Value in Manufacturing Companies in the Consumer Goods Sector Listed on the Indonesia Stock Exchange (IDX) in 2018-2022 - Ariana Delvira; Tri Darma Rosmala Sari (Indonesian Interdisciplinary Journal of Sharia Economics)
This study aims to explore the influence of several factors, namely Return on Assets (ROA), Debt to Equity Ratio (DER), and Good Corporate Governance (GCG) on the value of companies listed on the Indonesia Stock Exchange, especially in the property sector. The data used covers the period from 2015 to 2018, with analysis using the multiple regression method. The results of the study indicate that profitability as measured by ROA and leverage represented by DER have a significant influence on company value. The higher ROA indicates the company's ability to generate profits from its assets, which in turn increases its attractiveness to investors and the company's value. In addition, DER serves as an indicator of how much debt a company has compared to its equity; a lower ratio is generally considered better because it indicates lower financial risk. In addition, the quality of corporate management through GCG has also been shown to have an important role. Good GCG increases investor confidence and strengthens the relationship between profitability and company value. In other words, well-managed companies tend to have better financial performance, thus having a positive impact on their market value. Overall, this study confirms that these factors interact and contribute to the market valuation of companies in the Indonesian property sector.